ANALISIS PENGARUH KENDARAAN PARKIR DI BADAN JALAN SEBAGAI HAMBATAN SAMPING TERHADAP KINERJA RUAS JALAN MAHONI KOTA BENGKULU - Samsul Bahri; Rio Saputra; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2019)
Parking on the road body is one of the causes of traffic congestion, therefore the handling of parking on the road becomes very important and has a positive impact on solving traffic congestion problems. The purpose of this study was to determine the effect of parking vehicles on the road body on the performance of the Mahoni Street in Bengkulu City. Data collection methods and techniques include road geometric surveys, traffic volume surveys, side barriers and speed surveys. To get the data in this study is done by recording the state of the road and calculating the number of vehicles that cross the road through the recording.Data generated at peak hours in the form of a capacity of 1544,076 smp/hour traffic volume of 1281.2 sm / hour with a degree of saturation of 0.83 is at the level ofservice D which means approaching an unstable current, low speed. DS value is above the degree of saturation required by MKJI, namely DS <0.75. It is necessary to do alternative countermeasures by moving the parkinglocated on Mahoni Street resulting in a capacity of 2218.5 smp/hour and a saturation degree of 0.50 with level ofservice C which means that the current is stable and the speed is controlled by traffic.